Public Attitudes Toward Psychiatric Hospitals: A Rural-Urban Comparative Public Survey in Odisha State, India - Jena, Sunita; Zieger, Aron; Böge, Kerem; Salunkhe, Gayatri; Schomerus, Georg; Patel, Kripalini; Padhi, Bijaya Kumar; Ta, Thi Minh Tam; Mungee, Aditya; Hahn, Eric (Frontiers in Psychiatry, 2021)
Background: Integration of psychiatric care with public health services and offering mental health care services to patients from lower socioeconomic status remains a global challenge. Scarcity of funds and professional workforce in psychiatric hospitals contribute to this situation. However, negative attitudes in the population are also a known impediment to patients seeking mental health services. This study aimed to assess the attitudes toward psychiatric hospitals among the urban and rural population in India. Subjects and Methods: The study was carried out amongst the general population in Odisha, India. The total sample (n = 988) includes 496 respondents from an urban-setting, and 492 respondents from rural parts of the district. Participants were selected by using simple random-sampling from the Asian Institute of Public Health (AIPH) data base. A standardized seven-item questionnaire was adopted, with responses indicated on a 5-point Likert-scale. Interviews were fully structured and conducted face-to-face. Results: Level of education (B = −0.192, ß = −0.320, p < 0.000) and urban-rural comparison (B = −0.272, ß = −0.189, p < 0.000) significantly influenced attitudes toward psychiatric hospitals. Gender, age, and religious beliefs did not show any significant effect on attitudes toward psychiatric hospitals. Individuals in rural areas and those with lower education levels showed more negative attitudes toward psychiatric hospitals. Conclusion: Negative attitudes toward psychiatric hospitals from those living in rural areas as well as those with lesser education may be reflective of the lack of availability, accessibility, affordability, and credibility of such mental health services. The Mental Health Care Act in India is a progressive legislation which might improve the situation of the provided services and, consequently, reduce negative attitudes in the years to come.